Improving Aboriginal Women's Experiences of Antenatal Care: Findings from the Aboriginal Families Study in South Australia. Issue 1 (20th January 2015) - Brown, Stephanie Janne; Weetra, Donna; Glover, Karen; Buckskin, Mary; Ah Kit, Jackie; Leane, Cathy; Mitchell, Amanda; Stuart‐Butler, Deanna; Turner, May; Gartland, Deirdre; Yelland, Jane
Abstract Background Aboriginal and Torres Strait Islander families experience markedly worse maternal and child health outcomes than non‐Aboriginal families. The objective of this study was to investigate the experiences of women attending Aboriginal Family Birthing Program services in South Australia compared with women attending mainstream public antenatal care. Method Population‐based survey of mothers of Aboriginal babies giving birth in urban, regional, and remote areas of South Australia between July 2011 and June 2013. Results A total of 344 women took part in the study around 4–9 months after giving birth; 93 percent were Aboriginal and/or Torres Strait Islanders, and 7 percent were non‐Aboriginal mothers of Aboriginal babies. Of these, 39 percent of women lived in a major city, 36 percent in inner or outer regional areas, and 25 percent in remote areas of South Australia. Compared with women attending mainstream public antenatal care, women attending metropolitan and regional Aboriginal Family Birthing Program services had a higher likelihood of reporting positive experiences of pregnancy care (adjOR 3.4 [95% CI 1.6–7.0] and adjOR 2.4 [95% CI 1.4–4.3], respectively). Women attending Aboriginal Health Services were also more likely to report positive experiences of care (adjOR 3.5 [95% CI 1.3–9.4]). Conclusions In the urban, regional, and remote areas where the Aboriginal Family Birthing Program has been implemented, the program has expanded access to culturally responsive antenatal care for Aboriginal women and families. The positive experiences reported by many women using the program have the potential to translate into improved outcomes for Aboriginal families.